Factors Associated with Self-Management in Elderly Hypertensive Patients - Anisa Windiari; Dimas Ria Angga Pribadi (GLOBAL HEALTH SCIENCE GROUP, 2026)
Hypertension is a non-communicable disease that remains a major health problem in Indonesia and is a major risk factor for cardiovascular disease. The prevalence of hypertension in the elderly continues to increase, making self-management of this disease very crucial. One approach that has been proven effective is self-management, that includes adherence to medication, blood pressure monitoring, diet management, physical activity, and stress management. This study have to analyze the connection among demographic factors and the stage of self-management among elderly hypertensive patients at the Gabus District Health Center. The study employed a quantitative approach with a cross-sectional design. The study population consisted of all elderly hypertensive patients registered at the Gabus District Health Center. Purposive sampling was used, resulting in a total sample of 96 respondents. Data were collected using a questionnaire covering demographic characteristics and self-management components. The data were analyzed using descriptive statistics to summarize sample characteristics, Chi-square tests to examine relationships between variables, and logistic regression to identify the most dominant factors influencing self-management among elderly hypertensive patients.The outcome showed that age, education, income, in the process of of hypertension, and the presence of complications were substantially associated by the stage of self-management (p < 0.05). by the logistic regression test, income was proven to be the most dominant variable affecting self-management in elderly people by hypertension (OR = 7.082; 95% CI = 1.806-27.769). Health workers need to have appropriate education and support, whilst future researchers can having more effective self-management programs by considering these factors.